2008
DOI: 10.1055/s-2008-1067352
|View full text |Cite
|
Sign up to set email alerts
|

Beeinflusst der türkische Migrationshintergrund das Behandlungsergebnis?

Abstract: Study results indicate a higher psycho-social burden for people with a Turkish migration background who live in Germany. The present study researches, if such a burden difference is detectable at the beginning of an inpatient treatment program for patients with psychological/psychosomatic disorders, if different treatment progressions occur and asks which influence the factor migration background plays in terms of the treatment results. At admission patients with a Turkish migration background (N = 99 vs. N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 10 publications
0
3
0
5
Order By: Relevance
“…A previous study that did not assess language capacities has shown that Turkish migration background is an independent predictor for an unsuccessful rehabilitation treatment of patients with psychological or psychosomatic disorders in Germany [19]. The worrying finding of our study that 46.3% of T have the impression that their understanding of information given by the physician was “mediocre” or worse (G: 13.5%, see Table 3) could be an explanation to an unsuccessful treatment.…”
Section: Discussionmentioning
confidence: 54%
“…A previous study that did not assess language capacities has shown that Turkish migration background is an independent predictor for an unsuccessful rehabilitation treatment of patients with psychological or psychosomatic disorders in Germany [19]. The worrying finding of our study that 46.3% of T have the impression that their understanding of information given by the physician was “mediocre” or worse (G: 13.5%, see Table 3) could be an explanation to an unsuccessful treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Doch gerade für die Versichertengruppen, die aufgrund ihrer Sozialisation, ihrer Herkunft, ihres Ausbildungsstandes, ihres beruflichen Status, aber auch wegen ihrer Erkrankung oder Persönlichkeitsstruktur entweder in einer schwierigen sozialen oder beruflichen Situation stehen oder schon eine problematische beziehungsweise brüchige Erwerbsbiografie mitbringen, ist das psychosomatische Rehabilitationsangebot manchmal weniger nützlich oder Erfolg versprechend. Zur Gruppe der "schwierigen Patienten" in der psychosomatischen Rehabilitation gehören neben den Migranten zum Beispiel auch Arbeitslose, Erwerbsgeminderte, Versicherte mit somatoformen oder Persönlichkeitsstörungen und auch Langzeiterkrankte und Rentenantragsteller [19,27,31,32,33,34].…”
Section: Erreichbarkeit Von Und Effektivität Medizinisch-psychosomatiunclassified
“…Und auch Kobelt et al [17] beschreiben, dass die Schichtzugehörig-keit für die subjektive Prognose der Erwerbsfähigkeit eine größere Bedeutung hat als der Migrationshintergrund. [19,20,21,22]. In einer Untersuchung bei türkischstämmigen Rehabilitanden zeigte sich bei diesen -im Vergleich zu deutschstämmigen Versicherten -signifikant häufiger ein Rentenwunsch, oder es lag ein bereits gestellter Rentenantrag vor [22].…”
unclassified
“…Keywords: Culture, immigration, mental health, depression, psychotherapy ABSTRACT (13,14,15). For instance, studies conducted in Germany report lower rates of immigrant admissions to mental health care services than the admission rates of native population (13).…”
mentioning
confidence: 99%